Physical-chemical and microbiological analysis of curds sold in fairs in the city of Manaus-AM (Research, Society and Development, 2021)
Dairy products are consumed because they are healthy foods and have a high nutritional value. Among dairy products, curds have stood out for being sources of probiotics and bioactive compounds. The objective of this work was to carry out the physical-chemical and microbiological analysis of curds sold in fairs in the city of Manaus-AM. Ten samples of curds were collected in fairs in different zones: south-central (ZCS), east (ZL), north (ZN), west ZO) and south (ZS). These products were evaluated for their physicochemical characteristics (pH, total titratable acidity and moisture) and sanitary quality (presence of Coliforms at 45 °C, Escherichia coli and Salmonella sp.). The mean pH value was 3.63 and the significant acidity (0.48%) was verified in the ZN2 sample. The average moisture content of the analyzed samples was 89.14%. In samples ZL1 and ZCS2 were verified contamination by coliforms at 45 °C and E. coli, but no contamination by Salmonella sp. The presence of microorganisms that indicate fecal contamination point to the need for improvements in good manufacturing practices and the implementation of systems to monitor the sanitary quality of the curds sold in the city of Manaus.